(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The writer has described the role of women or the character of the female world in Englishliterature from twentieth century to the contemporary age of the twenty-first century in this STUDY. Thestudy depicts the progression of women’s features after the conclusion of World War I. This was the erawhen women learned to go outside of their comfort zones and were eager to break free from thestereotypes instilled around them by the masculine patriarchal system. Multiple new female authors withfeminist methods in mind have questioned the legendary approach or the strong masculine persona.